EXPLORING PHARMACY STUDENTS’ KNOWLEDGE AND UNDERSTANDING OF EATING DISORDERS AND THEIR IMPACT ON MENTAL HEALTH AND QUALITY OF LIFE - MAHMOOD, AQSA; BALL, PATRICK; MORRISSEY, HANA (International Journal of Current Pharmaceutical Research, 2021)
Objective: Eating disorders are a group of mental illnesses that are long-term and potentially life-threatening, affecting individuals’ physical and emotional health and wellbeing. They commonly exist alongside other mental health conditions such as depression and anxiety and are associated with a significant reduction in an individual's quality of life and life expectancy. They are poorly understood, and cases may be undiagnosed and thus untreated. This can result in damage to multiple organs, including the brain, heart, and kidneys. Methods: This was an online questionnaire-based study, which consisted of 21 open and closed-ended questions. Participants were from years 1 to 4 of the MPharm course at the University of Wolverhampton. Results: Fourty two completed surveys were returned. The results of the study revealed that pharmacy students lacked knowledge of eating disorders, which was also illustrated in previously conducted studies amongst other healthcare professions students. Therefore, it is evident that the current education about eating disorders is insufficient in many undergraduate healthcare courses and there is room for improvement. Conclusion: Improving future pharmacist’s knowledge about eating disorders would assist better and earlier identification of patients with such conditions, allowing timely support.